Does equity or bond offerings in Malaysia matter to share price performance? - Tern, Poh Joo; Lee, Hui Shan; Har, Wai Mun; Cheng, Fan Fah (2015)
This study examines the stock price reaction to the announcement of equity or bond issuance in Malaysia (2001 to 2011). Results reveal significant effect of equity issuance on the share price but insignificant effect of bond issuance on the share price. It suggests that the announcement of equity issuance conveys positive news to the investors as they perceive that the company requires more capital to finance the new huge project which could result in higher positive net present value. This result proposes to a large extend that equity market in Malaysia is semi-strong form efficient market hypothesis, there should be more prudent policies by the regulator to ensure the transparency in Malaysia’s equity market. This research also analyses the relationship between CAR with run up, issue size, leverage and financial slack. However, there is insignificant effect with the model inclusive of run up, issue size, leverage and financial slack towards CAR on equity or bond announcement.